The Role of Sovereign Ratings in M&A Markets: Empirical Evidence from Latin America and South East Asia. Issue 1 (19th January 2016) - Nguyen, Janna Mai; Knyphausen‐Aufseß, Dodo zu
Abstract : Sovereign ratings have not only been regarded as an indicator of country risk for foreign investors, but also as a determining factor for capital market conditions of domestic firms. Although they have attracted growing interest in academic research, the extant literature has so far rendered only minor attention to their role in corporate strategic investment decisions. This paper focuses on the influence of sovereign ratings on domestic and cross‐border M&A decisions in a sample of Latin American and South East Asian countries. The empirical results lend support to the proposition that sovereign ratings condition the level of activity in domestic M&A markets as well as the attractiveness of domestic M&A targets for foreign acquirers. Moreover, the foreign bidders' choice of ownership stakes in acquisitions appears to be affected. The paper thus highlights the relevance of sovereign ratings as a country‐level factor to be considered in studies of corporate investment behavior.